Kesantunan Berbahasa dalam Berwawancara Siswa SMK Satu Nusa 2 Bandar Lampung - Rohana, Rohana (JURNAL PESONA, 2017)
AbstractProblems in this research are politeness in English students class XI odd semester SMK Satu Nusa 2 Bandar Lampung academic year 2016-2017. Modesty speech is assessed based on some maxim, maximal admission, acceptance, generosity, humility, consent, and the maxim of conclusions. The purpose of research is to know the deviation of politeness in terms and views of the deviation factor. The research used descriptive with a qualitative approach. The subjects of this study were students of class XI who used 219 and only took 35 students as core subjects taken with proportionate stratified random sampling. The research data were collected by interviewing assignments and analyzed by qualitative analysis. The results showed there are deviations of politeness in students. Students are judged to be less wise speech so that develops the resource person. The deviation factor is being less able to formulate interview questions, narrow student vocabulary, and weak student interviewing abilities.Keywords: Modesty, language, interview